Implikasi Yuridis Parkir Sembarangan Yang Mengakibatkan Kecelakaan Dengan Korban Meninggal Dunia - Novia Dinda; syamsul Hidayat; Idi Amin (Juridische : Jurnal Penelitian Hukum, 2023)
This research purposes are to know and to understand how is the regulation of careless parking which causing accident with dead casualty, how is criminal responsibility of careless parking offender which caused such thing. Type of the study was normative legal research which applied statute, conceptual and case approaches. Result of the study shows that regulation on careless parking has been regulated under Law Number 22 of 2009 on Road Traffic, Art. 121 and 121 para (1) and (2), Government Regulation Number 32 of 2011 on Management, Engineering, Impact Analysis and Road Management, Government Regulation Number 37 of 2011 on Road and Traffic